Understanding competing discourses as a basis for promoting equity in primary health care - Amélie Blanchet Garneau; Annette J. Browne; Colleen Varcoe (BMC, 2019)
Abstract Background Globally, health inequities persist with effects on whole populations and the most profound effects on populations marginalized by poverty, discrimination and other forms of disadvantage. In the current neoliberal political-economic context, health inequities are produced and sustained by the inequitable distribution of social determinants of health and structural inequities such as discrimination and institutional racism. Even in the context of healthcare organizations with an explicit commitment to health equity, multiple intersecting discourses, such as ongoing efficiency discourses, and culturalist and racialized discourses, are in constant interaction with healthcare practices at the point of care and the organizational level, limiting providers' and organizations' capacities to address structural inequities. Attention to discourses that sustain inequities in health care is required to mitigate health inequities and related power differentials. In this paper, we present findings from a critical analysis of the relations among multiple discourses and healthcare practices within four Canadian primary health care clinics that have an explicit commitment to health equity. Methods Informed by critical theoretical perspectives and critical discourse analysis principles, we conducted an analysis of 31 in-depth interviews with clinic staff members. The analysis focused on the relations among discourses and healthcare practices, the ways in which competing discourses influence, reinforce, and challenge current practices, and how understanding these dynamics can be enlisted to promote health equity. Results We articulate the findings through three interrelated themes: equity-mandated organizations are positioned as the "other" in the health care system; discourses align with structures and policies to position equity at the margins of health care; staff and organizations navigate competing discourses through hybrid approaches to care. Conclusions This study points to the ways in which multiple discourses interact with healthcare organizations' and providers' practices and highlights the importance of structural changes at the systemic level to foster health equity at the point of care.